FEATURES OF THE ARBAIN GENRE, WRITTEN IN THE TURKIC LITERARY LANGUAGE IN THE XIV-XVI CENTURIES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
A special place is occupied by the transmission of religion through fiction. The foundations of Islam and the conditions of faith develop into true spirituality only when they are promoted as literary works. The poets who drew attention to this side wanted to glorify the verses of the Quran and the hadith of the Prophet through literature. Therefore, Arab, Persian and Turkic poets who wrote works within the framework of Islamic civilization wanted to convey the hadith of the Prophet Muhammad with an artistic word. The poets, who firmly adhered to the hadith of the Prophet: “Whoever gives Muslims forty hadiths from my hadiths will find paradise,” tried to convey the commandments of the Messenger of Allah to the next generation. As a result, the arbain genre emerged, which was widespread in the Middle Ages. Not to mention Arab and Persian writers, poets of the Turkic world, such as Imam al-Din Nasimi, Muhammad Fuzuli, Khazini and Alisher Navoi, conveyed forty selected hadiths of the Prophet in verse. Mahmut Kerderi, who lived in the Golden Horde, wrote forty hadiths in prose. In this work, Kerderi tried to reveal the inner content of the hadith. This tradition, which appeared in the Middle Ages, continued until the beginning of the twentieth century. This article analyzes the features of the arbain genre, written in the Turkic literary language in the XIV-XVI centuries.
Keywords: Middle Ages, Islamic literature, religious and didactic, hadith, genre, arbein, poetry, continuation of traditions.